Evaluation of Alternative Host Bacteria as Vehicles for Oral Administration of Bacteriophages - Bielke, L.R.; Higgins, S.E.; Donoghue, A.M.; Kral, T.; Donoghue, D.J.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2007)
Survival of bacteriophages through the upper gastrointestinal tract (UGIT) and persistence in the lower gastrointestinal tract (LGIT) is essential for treatment of enteric bacterial infections. We have hypothesized that non-pathogenic Alternative Host Bacteria (AHB), originally isolated from poultry cecal samples, could be used to protect bacteriophages during UGIT passage and to provide host cells for continued amplification in the LGIT. We selected two previously-identified Wide Host Range (WHR) bacteriophages (WHR-8 and WHR-10) and their respective AHB for use in the present studies. For each of the bacteriophage-host combinations, combination of the bacteriophage with the AHB prior to oral gavage had little effect on the concentration of recovered bacteriophages from the cecal contents during the three days post-administration. Furthermore, continuous administration of the AHB in the drinking water had little effect on intestinal bacteriophage recovery during the three days of evaluation. Bacteriophages were also tested for differences in anaerobic and aerobic lysis of Salmonella enteritidis as a possible reason for decreased persistence in the LGIT. Differences in lysis between anaerobic and aerobic environments were significant, however levels were not likely different enough to have significant in vitro effects. These results suggest that selection of AHB to protect or amplify enteric bacteriophage populations is not necessarily a simple process. Survival of the AHB and ability of the AHB to replicate in the LGIT of the target animals are among considerations that should be made in future investigations.